Transmitted Ellipsometry and DSC characterization of iPP/CNT nanocomposites crystallized isothermally at 135C - Cabrera, Yaniel. (Tufts Archival Research Center, 2005)
The purpose of this study is to characterize the morphology and crystallization kinetics of isotactic polypropylene, when it is used as a matrix in carbon nanotube based composites. We study the morphology of crystallization using microscopic transmission ellipsometry, a fast and efficient technique for studying anisotropic organization in polymers (Georgiev, 2002). Polymer carbon nanotube composites (PCNs) are the largest commercial application of carbon nanotubes (CNT) in nanotechnology. Isotactic polypropylene (iPP) is one of the best model systems to study in this field because iPP/CNT PCNs can form alpha, beta, and gamma crystallographic phases of iPP under a variety of crystallization conditions (Varga, 1992) including: nonisothermal and isothermal melt crystallization, shear, stress, and fiber extrusion. We measured iPP crystals growing perpendicularly to the surface of the CNTs. We present data for PCNs of varying concentrations of CNTs: 0%, 0.015, 0.1%, 1%, 2%, and 5%. We complement ellipsometry with differential scanning calorimetry for thermal analysis. For DSC studies we use the Avrami model of polymer crystallization to investigate the crystallization kinetics.